Inflation, Unemployment and Labor Force Change in Indonesia: What Does the Connection? - Nur Jamaluddin (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2021)
The issue of relationship between inflation and unemployment is one of the topics which have been discussed for long time. Philips Theory says that inflation rate has a relationship to unemployment rate, it becomes very interesting to observe the data of Indonesian Phenomena refer to the above theory therefore, this objective of this paper is to narrow the gap in literature by examining the long-run relationship between the change of labor force level, LF (t), inflation, ? (t), unemployment, UE (t), in Indonesia. It also to investigate the individual relationship between the change rate of LF and inflation, and change rate of LF and unemployment. Therefore, we use two different methods to test the cointegration. First is the Engle Granger approach based on the unit root test in the residuals of linear regression, which also includes a number of specification tests, Second method is the Johansen cointegration rank test based on a VAR representation, which is also proved to be an adequate one via a set of appropriate tests. This study used vector time series analysis to analyze the linear lag relationship between inflation, unemployment rate and the change in labor force participation. Under the empirical framework, the study adopted Vector Auto Regression (VAR) model. Results of this research, It is obtained from the Pearson correlation coefficient (correlation Pearson coefficient =0.059, for a significance level at 12% higher than the 5% the chosen one), that between the two variables there is a direct negative relationship, but of a very low and statistically insignificant medium intensity. This fact tell us to state that in the long run (23 years) between inflation and unemployment in Indonesia there is no significant relation. On the other hand, we noticed that there is also direct significant relationship between inflation and labor change. The Pearson coefficient = 0.080 for a significant level; at 13.5% greater than 5% from the chosen one, Which means that only 9.5% of the change in labor force was influenced by inflation. This denotes a very low and statistically insignificant medium intensity.